The jazz poetry anthology. [Volume 1] - Feinstein, Sascha, 1963-; Komunyakaa, Yusef (Bloomington : Indiana University Press, 1991)
Collection of hundreds of poems from writers across the United States responding to jazz in all its musical and cultural overtones.
Adult
Keywords: American poetry -- African American authors; American poetry -- 20th century; Jazz -- Poetry; American poetry -- African American authors; American poetry -- Collections; Jazz -- Poetry